2021
DOI: 10.3389/fneur.2021.700796
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits, Apathy, and Hypersomnolence Represent the Core Brain Symptoms of Adult-Onset Myotonic Dystrophy Type 1

Abstract: Myotonic dystrophy type 1 is the most common form of muscular dystrophy in adults, and is primarily characterized by muscle weakness and myotonia, yet some of the most disabling symptoms of the disease are cognitive and behavioral. Here we evaluated several of these non-motor symptoms from a cross-sectional time-point in one of the largest longitudinal studies to date, including full-scale intelligence quotient, depression, anxiety, apathy, sleep, and cerebral white matter fractional anisotropy in a group of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Alterations in white matter (WM) appear to occur early in the disease, as cerebral WM FA was found to be reduced among individuals with PreDM1, who have yet to manifest clinical motor symptoms ( 10 ). Reduced WM FA is associated with motor symptoms of DM1 ( 9 ), and with other functional outcomes, such as lower IQ, apathy and hypersomnolence ( 11 ). These studies underscore the importance of tracking brain health in DM1 to gain insights into disease onset and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in white matter (WM) appear to occur early in the disease, as cerebral WM FA was found to be reduced among individuals with PreDM1, who have yet to manifest clinical motor symptoms ( 10 ). Reduced WM FA is associated with motor symptoms of DM1 ( 9 ), and with other functional outcomes, such as lower IQ, apathy and hypersomnolence ( 11 ). These studies underscore the importance of tracking brain health in DM1 to gain insights into disease onset and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Myotonic dystrophy type 1 (DM1) is an inherited neuromuscular disease characterized by muscle rigidity, muscle weakness, and atrophy[ 1 - 3 ], with a prevalence of 0.5-18.1 per 100000 population[ 4 ]. DM1 patients may also have concurrent multiple systemic disorders, such as lens opacity[ 5 ], abnormal cardiac conduction systems[ 6 ], insulin resistance[ 7 ], gastrointestinal dysfunction[ 8 ], and cognitive dysfunction[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, sleep disturbances, including excessive daytime sleepiness, central and obstructive sleep apnea, restless legs syndrome, and rapid eye movement sleep dysregulation, are prominent in patients with DM1[ 12 , 13 ]. Overall, the clinical phenotype of DM1 patients is highly variable[ 1 , 6 , 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These central nervous system (CNS) deficits among DM1 individuals significantly increase the disease burden, not only affecting neuropsychological domains but also decreasing the whole quality of life. A large clinical longitudinal study of DM1 patients by Miller et al (2021) demonstrated that cognitive deficits, hypersomnolence, and apathy are critical brain symptoms of adult-onset DM1 caused by the underlying molecular mechanisms. In contrast, depression and anxiety are secondary coping symptoms with chronic physical and emotional stress ( Miller et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large clinical longitudinal study of DM1 patients by Miller et al (2021) demonstrated that cognitive deficits, hypersomnolence, and apathy are critical brain symptoms of adult-onset DM1 caused by the underlying molecular mechanisms. In contrast, depression and anxiety are secondary coping symptoms with chronic physical and emotional stress ( Miller et al, 2021 ). In addition, Simoncini et al (2020) proved that the severity and progression rate of neurological impairments are highly variable over time, possibly attributed to underlying neuropathology ( Mazzoli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%